USIA MENOPAUSE, RIWAYAT KONTRASEPSI, BERAT BADAN DENGAN TEKANAN DARAH PADA PEREMPUAN MENOPAUSE DI DESA ANGKATANLOR TAMBAKROMO PATI - noor hidayah; Hartatik Hartatik (Jurnal Ilmu Keperawatan dan Kebidanan, 2021)
Blood pressure is the most important part of the body’s circulation. Factors that affect blood pressure are hereditary factors, age, weight, gender, stress, unhealthy eating patterns, lack of physical activity, alcohol consumption, caffeine, smoking, history of hormonal contraceptive use, and other diseases. Indonesian Society of Hypertension (InaSH) survey conducted in may 2017 shows that hypertention cases tend to increase in erderly women. The purpose of this study was to determine the Relationship of age of menopause, contraceptive history, weight, withchanges in blood pressure in menopausal women in Angkatanlor Tambakromo Pati Village. This study was a quantitative research with correlational analysis and using a cross sectional and restropective approach. The sample used in this study was 120 respondents. Then, the data in this study was collected by questionnaire sheet by interview. The results of this study showed that there was relationship between age of menopause ( p = 0.001 ), history of hormonal contraceptive use (p = 0.000 ), weight ( p = 0.003 ) withchanges in blood pressure. Conclusion : Ha Accepted and Ho was rejected